Critical Analysis of the Implementation, Societal Conditions, and Issues Surrounding the Enforcement of Law No. 16 of 2019 Amending Law No. 1 of 1974 on Marriage in Indonesia - Novianti, Fatma; Prasetyo, Muhammad Imam; Maulana, Muhammad Zidan; Hidayah, Oktinyana Nurul (Universitas Negeri Gorontalo, 2024)
There are various problems that occur in the practice of implementing marriage related to the substance of the applicable Law, the lack of public understanding of the applicable regulations, causing problems to still occur, such as early marriage related to the age limit for marriage which is considered to still cause problems for one of the parties. Discrimination against women and the unfulfilled rights and obligations of each party after carrying out marriage, various studies related to the Marriage Law are carried out in order to improve the rules and public understanding of the regulations applied. This research method uses a qualitative descriptive explanation which describes the studies carried out and how the rules of the Law are applied and the problems that occur in society. The implementation of marriage carried out between women and men each has rights and obligations that must be fulfilled and implemented, but the age difference causes various problems in society, especially for women who have a lower age limit than men, causing discrimination against women and other problems such as health, economic, and social factors that are still not considered balanced, therefore it is necessary to conduct various studies regarding the Law related to marriage so that problems and practices in society are appropriate and evenly distributed.